Is There a Relationship Between Vascularity and Echogenicity of Thyroid Lobes in Ultrasonography With BMI? A Large Retrospective Cohort Study. (September 2022) - Sobhani, Sahar; Kalantari, Forough; Rasoul Zakavi, Seyed; Shafiei, Susan; Ebrahimi Miandehi, Elahe; Eslami, Saeed; Aghaee, Atena
Objective: The aim of this study was to investigate the relationship between sonographic vascularity and echogenicity of the thyroid lobes, compared with a participant's body mass index (BMI). Materials and Methods: A total of 3722 participations, with varied BMI, were included in the study. For all the participants, the thyroid-stimulating hormone (TSH) was measured, as well as thyroid volume, sonographic echogenicity, and vascularity were recorded. A multiple regression analysis was performed to assess the relationship between the sonographic vascularity and echogenicity, of thyroid lobes, compared with the participants' BMI. Results: The serum TSH values were significantly higher in patients with a BMI > 25 kg/m². The sonographic vascularity and volume of thyroid lobes were positively correlated the participants' BMI ( P < .005). Sonographic heterogenicity of the left thyroid lobe, right thyroid lobe, and the isthmus were positively associated with BMI ( P < .005). However, the hyper/hypoechogenicity did not demonstrate any significant correlation with BMI ( P > .005). Conclusion: Based on the findings of this study, it was concluded that thyroid volumes may have a significant positive relationship with BMI. In overweight participants (i.e., BMI more than 25), thyroid echogenicity was more heterogeneous and their thyroid lobes were more hypovascular.